How In-store Marketing Affects Purchase and Salesman's Recommendation Rate in Telecom Retail Stores - Karabıyıkoglu, Melik (International Review of Management and Marketing, 2012)
The authors study in-store marketing for telecom retail stores in GSM sector in Turkey which handset manufacturers practice special application in stores for increasing purchasing and improving suggestion rates of their products. They develop a theoretical model of dealers, and manufacturers behavior based on observations about key aspects of the mobile phone market. The analysis provides important insights about in-store marketing and their applications. For example, owner of the store and salesmen would like to support in-store marketing applications of manufacturers in spite of operators’s in-store rules. The authors find empirical support when they test the theoretical results. Keywords: In-store marketing; Recommendation rate; Retail Marketing; Trade marketing; Wireless Industry JEL Classifications: M3; M37